Fungal endophytes as the source of medicinal natural product - Asih Triastuti (Jurnal Ilmiah Farmasi, 2020)
AbstractMassive exploration of medicinal plants as a source of medicinal raw materials and high demand for traditional medicines on the market has been a threat to biodiversity and plant species. To respond to the challenge of more efficient access to chemical diversity in a sustainable way, researchers have begun to focus their research on renewable sources, under-explored, but that have the prospect as the reservoir of new structures of bioactive metabolites, namely fungal endophytes. Fungal endophytes grow within the internal tissue s of the plant, without causing pathogenic symptoms have succeeded in producing secondary metabolites with diverse chemical structures and pharmacological activities such as antibacterial, antifungal, insecticide, antioxidant, anti hyperlipidemia, cytotoxic and anticancer. However, under conventional laboratory conditions, a plethora of secondary metabolites encoded in fungal endophytes were not produced presumably because the genes responsible for the secondary metabolites biosynthetic are not transcribed (remain silent). Several methods have been explored to activate these silent genes, including optimization parameters of fermentation, co-culture techniques, precursors/ plant extracts feeding, the addition of epigenetic modifiers such as DNA methyltransferase (DNMT) or histone deacetylase (HDAC) inhibitors, and genetic manipulation of biosynthetic and regulatory genes. The approaches in culture techniques are expected to bridge the debate in drug discovery and natural material production from endophytic fungi.Intisari Eksplorasi besar-besaran tanaman obat sebagai sumber bahan baku obat dan tingginya permintaan akan obat tradisional di pasaran telah menimbulkan permasalahan dalam biodiversitas dan ancaman bagi spesies tanaman. Peneliti bahan alam telah mulai memfokuskan penelitannya pada sumber terbarukan yang belum tereksplorasi namun memiliki prospek sebagai penyedia keanekaragaman struktur kimia, yaitu jamur endofit. Jamur endofit hidup di dalam jaringan tanaman tanpa menimbulkan simptom patogenik dan telah dilaporkan menghasilkan metabolit sekunder dengan struktur kimia yang beragam dengan aktivitas farmakologi yang luas seperti antibakteri, antijamur, insektisida, antioksidan, antihiperlipidemia, sitotoksik dan antikanker yang sangat potensial untuk dikembangkan dalam industri farmasi. Dalam pengembangannya, pemanfaatan jamur endofit memiliki beberapa kendala, utamanya dalam teknik kultur / fermentasi dalam rangka mengaktifkan gen penyandi biosintesis metabolit sekunder yang relatif inaktif selama kultur. Metode untuk mengaktifkan gen diam (silent gene) dapat dilakukan dengan beberapa cara yaitu: optimasi parameter fermentasi, teknik ko-kultur, penambahan prekursor atau zat antara ke dalam media kultur, penambahan modifikator epigenetik seperti inhibitor DNA methyltransferase (DNMT) dan atau inhibitor histone deacetylase (HDAC), dan manipulasi genetik. Pendekatan dalam teknik kultur jamur endofit diharapkan dapat menjembatani permasalahan dalam penemuan obat dan produksi bahan alam dari jamur endofit. Kata kunci: Jamur endofit, Aktivitas farmakologi, Aktivasi gen diam